(untitled) (Revista Brasileira de Contabilidade e Gestão, 2014)
The intense competition among economic agents, especially in the last decades has changed the conceptual bases that determine the rules of market action, requiring the design of new parameters for strategic positioning. Among them figure out innovation as a way to migrate from the paradigm of competition based on cost, toward differentiation, and environmental management, in response to the deterioration of the environment as a result of uncontrolled industrialization. However the extent that innovation stimulates the growth of consumption reduces the life cycle of products and increases the amount of the waste, with environmental management promoting an opposite view, in favor of the mitigation of the environmental impact. In order to investigate the alternatives of combining process innovation with environmental practices in the industrial organizations was performed multiple case study in three organizations by qualitative study, interviews and analysis of narratives. The results showed that the form adopted by organizations to innovate processes in combination with the environmental practices depends on the strategic positioning, internal structure and the resources available for investment.